The State and the legalist press: 40 years under pressure (1864–1904) - Rybin, Danil V. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
In the second half of the 19th – early 20th centuries, the legalist (juridical) press played a prominent role in the Russian liberation movement. Its leading publications professed the principles of legality and law and order. In fact, the term “Order” itself appeared thanks to the newspaper of the same name, and supporters of legalism were called “people of legal order”. Despite the objectively statist nature of the legalist press, the conservative part of the bureaucracy could not accept these moderately progressive ideas and in the 1880s went on the offensive against legalist publications. Part of the legal press was closed, the other survived under heavy daily censorship pressure.